Inhibitory control performance is repeatable over time and across contexts in a wild bird population. (May 2022) - Davidson, Gabrielle L.; Reichert, Michael S.; Coomes, Jenny R.; Kulahci, Ipek G.; de la Hera, Iván; Quinn, John L.
Abstract : Inhibitory control is one of several cognitive mechanisms required for self-regulation, decision making and attention towards tasks. Inhibitory control is expected to influence behavioural plasticity in animals, for example in the context of foraging, social interaction or responses to sudden changes in the environment. One widely used inhibitory control assay is the 'detour task' where subjects must avoid impulsively touching transparent barriers positioned in front of food, and instead access the food by an alternative but known route. However, because the detour task has been reported to measure factors unrelated to inhibitory control, including motivation, previous experience and persistence, the task may be unreliable for making cross-species comparisons, estimating individual differences and linking performance with socioecological traits. To address these concerns, we designed a variant of the detour task for wild great tits, Parus major, and deployed it at the nesting site across two spring seasons. We compared task performance of the same individuals in the wild across 2 years, and with their performance in captivity when tested using the classical cylinder detour task during the nonbreeding season. Potential confounds of motivation, previous experience, body size, sex, age and personality did not significantly predict performance, and temporal and contextual repeatability were low but significant. These results support the hypothesis that our assays captured intrinsic differences in inhibitory control. Instead of dismissing detour tasks and 'throwing the baby out with the bathwater', we suggest confounds are likely system and experimental-design specific, and that assays for this potentially fundamental but largely overlooked source of behavioural plasticity in animal populations, should be validated and refined for each study system. Highlights: The detour task is a widely used measure of inhibitory control in animal cognition. Individual consistency across wild and captive contexts has never been explored. We compared a traditional detour task with one that was deployed at bird nestboxes. Performance was consistent across wild and captive contexts and across years. Individual performance was not sensitive to bias from extraneous influences.